A national clinician–educator program: a model of an effective community of practice - Sherbino, Jonathan (Medical Education Online, 2010)
BACKGROUND: The increasing complexity of medical training often requires faculty members with educational expertise to address issues of curriculum design, instructional methods, assessment, program evaluation, faculty development, and educational scholarship, among others. DISCUSSION: In 2007, The Royal College of Physicians & Surgeons of Canada responded to this need by establishing the first national clinician–educator program. We define a clinician–educator and describe the development of the program. Adopting a construct from the business community, we use a community of practice framework to describe the benefits (with examples) of this program and challenges in developing it. The benefits of the clinician–educator program include: improved educational problem solving, recognition of educational needs and development of new projects, enhanced personal educational expertise, maintenance of professional satisfaction and retention of group members, a positive influence within the Royal College, and a positive influence within other Canadian academic institutions. SUMMARY: Our described experience of a social reorganization – a community of practice – suggests that the organizational and educational benefits of a national clinician–educator program are not theoretical, but real.